Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper investigates the factors behind the deterioration in Italy's international competitiveness. It concludes that the loss of competitiveness accumulated by Italian firms in recent years is mainly a consequence of weak long-term productivity performance. The paper explores the link between policies and growth. Specifically, it finds evidence that rigid product markets and a high tax burden on labor have been associated with slower growth in European regions. The paper also analyzes the role of fiscal policy and its implications for household consumption decisions.